Sewing Technology And Energy Saving Technologies In Automatic Design Problems - Vafaeva Zamira Sevindikovna (Research Parks Publishing LLC, 2021)
In this article,, the technology of sewing production and the application of energy-saving technologies in automatic design, information about the problems.